Copper-ceramic bonded substrate and method for manufacturing the same

CN118742527BActive Publication Date: 2026-10-27DOWA METALTECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280092342.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-03-14
Filing Date
2022-11-21
Publication Date
2026-10-27
Estimated Expiration
2042-11-21

AI Technical Summary

Technical Problem

若使用Al,则施加通炉处理或热循环等的热负荷,能够通过Al塑性变形来缓和因陶瓷基板与金属电路板的热膨胀差而产生的热应力,但在导电性、散热性方面比Cu的金属电路板差

Benefits of technology

[0039]根据本发明,在铜-陶瓷接合基板中,即使不变更外形尺寸,也能够实现良好的热循环特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118742527B_ABST
    Figure CN118742527B_ABST
Patent Text Reader

Abstract

A copper-ceramic bonded substrate includes a ceramic substrate and a copper plate bonded to at least one face of the ceramic substrate, the copper plate having a dislocation density of 1.5 x 10 13 m ‑2 The following.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to copper-ceramic bonding substrates and methods for manufacturing the same. Background Technology

[0002] Power modules are used to control the large amounts of electricity in electric vehicles, trams, and machine tools. The circuit board for such power modules is a metal-ceramic bonding substrate, where a metal circuit board, such as Cu or Al, is bonded to the surface of a ceramic plate. A circuit pattern metal plate is formed on one side of the ceramic substrate of this metal-ceramic bonding substrate, and a heat-dissipating metal plate is formed on the other side.

[0003] As a method for manufacturing such a metal-ceramic bonding substrate, there is a known method that involves placing a solder (Ag-Cu active metal solder) mixed with an active metal, Ag, and Cu in between, and bonding the metal plate to the ceramic by heat treatment (active metal brazing method) (for example, see Patent Document 1).

[0004] Repeated thermal loads are applied to the metal-ceramic bonding substrate used in power modules during the assembly process and in the actual use environment of the power modules.

[0005] For example, in the assembly process of a power module, power semiconductor components are mounted on the circuit pattern metal plate using bonding methods such as soldering or microparticle metal sintering. Additionally, a substrate such as a Cu, Al, or Al-SiC composite material is bonded to the heat dissipation metal plate using the same bonding method. At this time, heating is performed, for example, by passing the furnace through a tunnel (continuous) furnace, thus applying a heat load from the furnace treatment to the bonding substrate.

[0006] In addition, for example, in actual use of power modules, power semiconductor components generate heat due to switching operations and are cooled when the power module stops operating, thus applying a thermal load of thermal cycling to the power module.

[0007] Circuit boards using metal-ceramic bonding substrates may employ Cu or Al, for example. When Al is used, applying thermal loads such as furnace treatment or thermal cycling can mitigate thermal stress caused by the difference in thermal expansion between the ceramic substrate and the metal circuit board through Al's plastic deformation. However, Al's conductivity and heat dissipation are inferior to those of Cu-based metal circuit boards. On the other hand, when using Cu as the metal circuit board, compared to using Al, there is a problem of lower reliability under thermal loads.

[0008] Therefore, copper-ceramic bonding substrates are required to have good thermal cycling characteristics that are not easily damaged even when these heat loads are applied.

[0009] As a method to mitigate thermal stress on ceramics caused by heat load, a method has been proposed to provide a stepped shape in the cross-sectional shape of the metal plate to which it is joined with the ceramic (for example, see Patent Document 2), and a method to provide a recessed shape on the outer periphery of the metal plate to which it is joined with the ceramic (for example, see Patent Document 3).

[0010] Existing technical documents

[0011] Patent documents

[0012] Patent Document 1: Japanese Patent Application Publication No. 8-97554

[0013] Patent Document 2: Japanese Patent Application Publication No. 10-125821

[0014] Patent Document 3: Japanese Patent Application Publication No. 2012-114203 Summary of the Invention

[0015] The problem the invention aims to solve

[0016] However, in the methods disclosed in Patent Document 2 or 3, the mounting area of ​​electronic components mounted on the surface of the metal plate is reduced, thus necessitating an increase in the external dimensions (area) of the copper-ceramic bonding substrate, sometimes leading to larger power modules.

[0017] Therefore, the object of the present invention is to provide a technology that can achieve good thermal cycling characteristics even without changing the external dimensions of the copper-ceramic bonding substrate.

[0018] Solution for solving the problem

[0019] A first aspect of the present invention is a copper-ceramic bonding substrate comprising: a ceramic substrate; and a copper plate bonded to at least one side of the ceramic substrate, the copper plate having a dislocation density of 1.5 × 10⁻⁶. 13 m -2 the following.

[0020] The second aspect of the present invention is that, in the first aspect, the arsenic content in the copper plate is 0.005ppm to 1.5ppm, and the antimony content is 0.005ppm to 0.5ppm.

[0021] The third aspect of the present invention is that, in the first or second aspect, the sulfur content in the copper plate is 0.1 ppm to 7 ppm and the phosphorus content is 0.05 to 2 ppm.

[0022] The fourth aspect of the present invention is that, in aspects 1 to 3, the zinc content in the copper plate is 0.005 ppm to 0.08 ppm.

[0023] The fifth aspect of the present invention is that, in aspects 1 to 4, the silver content in the copper plate is 0.1 ppm to 20 ppm.

[0024] The sixth aspect of the present invention is that, in aspects 1 to 5, the total amount of impurity elements in the copper plate other than sulfur, phosphorus, arsenic, antimony, zinc and silver is 0.01 ppm to 15 ppm.

[0025] The seventh aspect of the present invention is that, in aspects 1 to 6, the copper plate is made of oxygen-free copper or ductile copper.

[0026] The eighth aspect of the present invention is that, in aspects 1 to 7, a solder bonding layer is provided between the ceramic substrate and the copper plate, and the copper plate sandwiches the solder bonding layer and is bonded to the ceramic substrate.

[0027] The ninth aspect of the present invention is a method for manufacturing a copper-ceramic bonding substrate, comprising the following bonding step: placing a copper plate with an arsenic content of 0.005 ppm to 1.5 ppm and an antimony content of 0.005 ppm to 0.5 ppm on at least one side of a ceramic substrate and bonding them by heating, wherein the dislocation density of the copper plate after bonding is 1.5 × 10⁻⁶. 13 m -2 the following.

[0028] The tenth aspect of the present invention is that, in the ninth aspect, during the bonding process, the copper plate is disposed on the ceramic substrate, and the ceramic substrate and the copper plate are heated under temporary pressure.

[0029] The eleventh aspect of the present invention is that, in the ninth or tenth aspect, the sulfur content in the copper plate is 0.1 ppm to 7 ppm and the phosphorus content is 0.05 to 2 ppm.

[0030] The 12th aspect of the present invention is that, in aspects 9 to 11, the zinc content in the copper plate is 0.005 ppm to 0.08 ppm.

[0031] The 13th aspect of the present invention is that, in aspects 9 to 12, the silver content in the copper plate is 0.1 ppm to 20 ppm.

[0032] The 14th aspect of the present invention is that, in aspects 9 to 13, the total amount of impurity elements in the copper plate other than sulfur, phosphorus, arsenic, antimony, zinc and silver is 0.01 to 15 ppm.

[0033] The 15th aspect of the present invention is that, in aspects 9 to 14, the copper plate is made of oxygen-free copper or ductile copper.

[0034] The 16th aspect of the present invention involves, in aspects 9 to 15, placing the copper plate sandwiching the solder on the ceramic substrate and then heating it to join them.

[0035] The 17th aspect of the present invention is that, in aspects 9 to 16, the joining process is performed by heating in a temperature range of 500°C or higher for 6 hours or more.

[0036] The 18th aspect of the present invention is that, in aspects 9 to 17, the joining process is performed by heating in a temperature range of 700°C or higher for more than 2 hours.

[0037] The 19th aspect of the present invention is that, in aspects 9 to 18, the temporary pressurization load pressure in the joining process is 0.5 kPa to 5 kPa.

[0038] The effects of the invention

[0039] According to the present invention, good thermal cycling characteristics can be achieved in copper-ceramic bonding substrates without changing the external dimensions. Attached Figure Description

[0040] Figure 1 This is a cross-sectional view schematically illustrating an example of a copper-ceramic bonding substrate according to one embodiment of the present invention.

[0041] Figure 2 This is a schematic diagram illustrating the shape of a circuit pattern formed on one side of the bonding substrate in an embodiment.

[0042] Figure 3 This is a schematic diagram illustrating the shape of a heat sink pattern formed on another side of the bonding substrate in an embodiment. Detailed Implementation

[0043] <Insights obtained by the inventors, etc.>

[0044] First, the insights obtained by the inventors will be explained.

[0045] The copper plates used in copper-ceramic bonding substrates (hereinafter referred to as bonding substrates) are usually pure copper plates with a purity of 99.9% by mass or higher, such as oxygen-free copper (C1020) or tough copper (C1100). However, it has been found that even when using copper plates of the same specifications (the same type of pure copper and the same material), the thermal cycling properties of the final copper-ceramic bonding substrate are different.

[0046] This point was studied and investigated, and the results indicate that the amount of trace impurity elements contained in the cast copper ingot before rolling, as well as the manufacturing conditions such as rolling and heat treatment, vary depending on each copper sheet manufacturer. Therefore, the results of measuring the distortion accumulation state (dislocation accumulation state) in the copper sheet show that the dislocation density of the copper sheet in the copper-ceramic bonding substrate varies depending on the manufacturer, the casting of the copper ingot, and other manufacturing conditions. When the copper sheet is bonded to the ceramic substrate, it is annealed at a temperature above the softening temperature of copper (e.g., 200°C), thus reducing the dislocation accumulation in the copper sheet. However, the dislocation accumulation state of the copper sheet before bonding and the amount of trace impurity elements affecting annealing vary depending on the manufacturer and the manufacturing conditions of the copper ingot. Therefore, the recovery, recrystallization, and grain growth of copper crystals in the bonding process of the bonding substrate also differ, which is presumably related to the thermal cycling properties of the final bonded substrate.

[0047] Therefore, the inventors quantitatively evaluated the accumulation state of distortion in a copper plate using the modified Williamson-Hall / Warren-Averbach method to measure dislocation density, and further investigated the correlation between the dislocation density and the amount of impurity elements in the copper plate, as well as the thermal cycling properties of the bonding substrate.

[0048] The results showed that high thermal cycling characteristics could be obtained by adjusting the dislocation density of the copper plate in the copper-ceramic bonding substrate to below a specified value. Furthermore, it was found that by controlling the content of specific impurity elements in the copper plate within a certain range, the dislocation density of the copper plate in the bonding substrate could be reduced.

[0049] Furthermore, as a method for manufacturing such a copper-ceramic bonding substrate, a method for manufacturing a copper-ceramic bonding substrate can be provided in which, after placing a copper plate on at least one side of a ceramic substrate and heating it, the dislocation density of the bonded copper plate is set to a predetermined value or below, and a copper plate in which the content of a specific impurity element contained in the copper plate is controlled within a certain range is used, thereby enabling the dislocation density in the copper plate of the bonding substrate to be controlled to be relatively small.

[0050] When the dislocation density in the copper plate is high, it is believed that during thermal cycling of the copper-ceramic bonding substrate, the dislocations accumulated in the copper plate will hinder the sliding movement of the copper crystals, making the copper plate prone to work hardening. Therefore, it is speculated that during thermal cycling, the thermal stress applied to the ceramic substrate of the copper-ceramic bonding substrate increases, and its thermal cycling performance decreases. Regarding this point, it has been found that by controlling the content of impurity elements in the copper plate to a specified range within the dislocation density of the copper plate in the copper-ceramic bonding substrate, high thermal cycling performance can be achieved in the bonding substrate.

[0051] This invention is based on the above insights.

[0052] <One embodiment of the present invention>

[0053] Hereinafter, embodiments of the copper-ceramic bonding substrate according to the present invention will be described with reference to the accompanying drawings. Figure 1 This is a cross-sectional view schematically illustrating an example of a copper-ceramic bonding substrate according to one embodiment of the present invention. It should be noted that the present invention is not limited to these examples, and as shown in the claims, it is intended to include all modifications within the meaning and scope equivalent to the claims. Furthermore, the numerical range indicated by “~” in this specification refers to the range of values ​​described before and after “~” as a lower and upper limit value.

[0054] (1) Copper-ceramic bonding substrate

[0055] First, the copper-ceramic bonding substrate will be described. Here, the case where a copper plate is bonded to both sides of a ceramic substrate will be used as an example. It should be noted that in this specification, "copper-ceramic bonding substrate" refers to both the pre-circuit fabrication substrate before the circuit pattern is formed on the copper plate and the circuit substrate after the circuit pattern is formed on the copper plate. Hereinafter, "copper-ceramic bonding substrate" will also be simply referred to as "bonding substrate".

[0056] like Figure 1 As shown, the copper-ceramic bonding substrate 1 (bonding substrate 1) of this embodiment is, for example, composed of a ceramic substrate 10, a solder bonding layer 11, and a copper plate 12. The bonding substrate 1 is processed into a copper-ceramic circuit board (hereinafter also referred to as a circuit board) by forming a predetermined pattern on the copper plate 12.

[0057] (Ceramic substrate)

[0058] The ceramic substrate 10 is used to support and fix the copper plate 12, thereby providing insulation between circuits or between the front and back surfaces when used as a circuit substrate. For example, an oxide-based ceramic substrate with aluminum oxide as the main component, or a non-oxide-based ceramic substrate with aluminum nitride, silicon nitride, silicon carbide, or similar components can be used as the ceramic substrate 10. Regarding the size of the ceramic substrate 10, a ceramic substrate with a length of 5mm to 200mm, a width of 5mm to 200mm, and a thickness of 0.2mm to 3.0mm is preferred; a generally rectangular ceramic substrate with a length of 10mm to 100mm, a width of 10mm to 100mm, and a thickness of 0.25mm to 2.0mm is more preferable.

[0059] (Breaker joint layer)

[0060] A solder bonding layer 11 is provided on both sides of the ceramic substrate 10. The solder bonding layer 11 is located between the ceramic substrate 10 and the copper plate 12 and is used to bond them together. The solder bonding layer 11 is formed, for example, from a solder containing silver and copper as metallic components and also containing active metal components (a solder containing active metal). The solder bonding layer 11 is a layer formed by the reaction of the components of the ceramic substrate 10, the solder, and the copper plate 12 in the bonding process described later.

[0061] The thickness of the solder bonding layer 11 is not particularly limited, but from the viewpoint of ensuring the thermal shock resistance and bonding of the circuit board made from the bonding substrate 1, it is preferably 3μm to 50μm, and more preferably 5 to 20μm.

[0062] The silver content in the solder is not particularly limited, but from the viewpoint of improving the reliability of the solder bonding layer 11, such as the bonding strength, it is preferably 30 to 95% by mass, more preferably 50 to 90% by mass, and even more preferably 65 to 90% by mass. Furthermore, the silver content in the solder refers to the mass ratio relative to the total mass of the metal components contained in the solder. Hereinafter, the content of metal components other than silver is also a proportion relative to the total mass of the metal components contained in the solder.

[0063] As an active metal component, it is preferable to include at least one active metal selected from titanium or zirconium. The content of the active metal component in the solder is preferably 1.0 to 7.0% by mass, more preferably 1.5 to 6.5% by mass. This improves and ensures the bonding strength between the ceramic substrate and the copper plate. In the case where the solder containing the active metal is silver-copper based, the remaining metal component (other than silver and the active metal component) is copper.

[0064] It should be noted that, from the viewpoint of reducing bonding defects and suppressing migration, the solder can further include tin as a metallic component. The tin content, for example, can be set to 10% by mass or less relative to the total amount of metallic elements. Based on tin, the bonding strength between the ceramic substrate and the copper plate can be further improved. That is, in the case of silver-copper based solders containing active metals, for example as described above, it is preferable that the solder's metallic composition contains 30-95% by mass of silver, 1.0-7.0% by mass of active metals, 10% by mass or less of tin (preferably 1-8% by mass), and the remainder is composed of copper.

[0065] (copper coin)

[0066] Copper plates 12 are bonded to both sides of a ceramic substrate 10 by solder bonding layers 11. The copper plates 12 are plate-shaped components made of pure copper containing copper and impurity elements. One of the copper plates 12, copper plate 12a bonded to one side, is used to form a predetermined circuit pattern. The copper plate 12b bonded to the other side is used to form a heat sink pattern, which dissipates heat generated by chip components such as semiconductor elements mounted on the circuit pattern.

[0067] From the viewpoint of improving thermal conductivity and achieving high heat dissipation, the copper plate 12 is preferably pure copper with a copper (Cu) content of 99.9% by mass or more, and more preferably 99.96% by mass or more. Furthermore, the copper plate 12 may contain impurity elements such as silver (Ag), iron (Fe), zinc (Zn), phosphorus (P), sulfur (S), arsenic (As), and antimony (Sb).

[0068] (Impurity elements in copper plates)

[0069] When elements are added to copper, it is generally believed that most of these elements raise the recrystallization temperature of copper and hinder its recrystallization during heating. Since the impurity elements in pure copper are present in trace amounts, it is not always possible to definitively confirm an increase in the recrystallization temperature of copper. However, it is speculated that they may affect the movement and disappearance of dislocations during heating when bonding copper plates to ceramic substrates.

[0070] Regarding this point, according to the research of the inventors, S, P, As, Sb, and Zn are elements that have a particularly significant impact on the movement and disappearance of dislocations in Cu. For example, S tends to be unevenly distributed at the grain boundaries of Cu, and tends to hinder the movement and disappearance of dislocations when Cu is heated. In this regard, the researchers of the present invention have found that it is preferable to control the S content in the copper plate 12 to 0.1 ppm to 7 ppm, the P content to 0.05 ppm to 2 ppm, the As content to 0.005 ppm to 1.5 ppm, the Sb content to 0.005 ppm to 0.5 ppm, and the Zn content to 0.005 ppm to 0.08 ppm. By controlling these contents, it is possible to suppress the movement and disappearance of dislocations in Cu (or the increase in recrystallization temperature). It is believed that with a copper plate 12 having this composition, it is easier to reduce the dislocations accumulated internally during heating, and work hardening caused by thermal cycling can be suppressed. That is, the thermal cycling performance of the copper-ceramic bonding substrate 1 can be further improved. It should be noted that the impurity ratio refers to "mass ppm", but is expressed as "ppm" for convenience. Additionally, as shown in the examples described later, the impurity content is expressed as a value determined by glow discharge mass spectrometry (GDMS).

[0071] The content of each impurity element is explained below.

[0072] The content of S is preferably 0.1ppm to 7ppm, and from the viewpoint of improving the thermal cycling performance of the bonding substrate 1, it is more preferably 1ppm to 6ppm, and even more preferably 4.5ppm or less.

[0073] It is known that phosphorus (P) and sulfur (S) are similarly unevenly distributed at the grain boundaries of Cu, causing an increase in recrystallization temperature. However, according to the research of the inventors, it has been found that P helps to suppress the increase in recrystallization temperature through its interaction with S. Therefore, P can be present in the presence of S, and the content of P can be 0.05 ppm to 2 ppm or 0.1 to 1.5 ppm.

[0074] The content of As is preferably 0.005ppm to 1.5ppm, more preferably 0.05ppm to 0.5ppm, and may also be less than 0.3ppm.

[0075] The Sb content is preferably 0.01ppm to 0.5ppm, more preferably 0.02ppm to 0.2ppm.

[0076] The Zn content is preferably 0.005ppm to 0.08ppm, more preferably 0.01ppm to 0.04ppm.

[0077] In addition to S, P, As, Sb, and Zn, copper plate 12 may also contain Ag. It is considered that the effect of Ag on the movement and disappearance of dislocations in Cu (or the increase in recrystallization temperature) during heating of the copper plate is negligible. Therefore, it may contain less than 20 ppm of Ag. Preferably, it is 0.1 ppm to 15 ppm, or 1 to 10 ppm.

[0078] Furthermore, the content of impurity elements other than those mentioned above is not particularly limited, and the total content of impurity elements is preferably 0.01ppm to 15ppm, more preferably 0.1ppm to 8ppm, and most preferably 0.5ppm to 6ppm. In addition, the total content of impurity elements can be 3ppm or less.

[0079] The copper plate 12, having the above composition, bonded to the ceramic substrate, is configured such that the dislocation density determined by the modified Williamson-Hall / Warren-Averbach method (hereinafter also referred to as the mWH / WA method) is 1.5 × 10⁻⁶. 13 m -2 The preferred dislocation density is 1.0 × 10⁻⁶. 13 m -2 the following.

[0080] It should be noted that a lower dislocation density is preferred, and there is no specific limit to its lower limit; for example, the lower limit could be 1.0 × 10⁻⁶. 11 m -2 or 1.0×1012 m -2 .

[0081] The mWH / WA method is a type of X-ray diffraction profilometry. X-ray diffraction profilometry is a method that quantitatively evaluates factors such as crystallite size, lattice distortion, and dislocation density—which are factors causing shape changes—by inversely analyzing the shape of the X-ray line profile (diffraction intensity curve). According to the mWH / WA method, by introducing a correction term called the contrast factor to account for the influence of lattice distortion, which depends on crystal orientation, the dislocation density can be quantitatively evaluated with higher precision.

[0082] In this embodiment, by controlling the content of specific impurity elements in the copper plate 12 within a specified range, the number of dislocations in the copper plate decreases during heating, and the dislocation density of the copper plate 12 bonded to the ceramic substrate 10, calculated using the mWH / WA method, becomes 1.5 × 10⁻⁶. 13 m -2 the following.

[0083] Furthermore, the copper plate 12 undergoes recrystallization of Cu through heating during bonding, thereby increasing the average grain diameter of Cu to be larger than before bonding. In the copper plate 12 of this embodiment, the contents of P, S, As, Sb, and Zn are controlled within a specified range, thus dislocations are easily reduced by heating, further increasing the average grain diameter of Cu after heating. The average grain diameter of Cu is not particularly limited, but from the viewpoint of further improving thermal cycling performance, it is preferably 0.05 to 0.5 mm, more preferably 0.08 to 0.4 mm.

[0084] It should be noted that the two copper plates 12 used in the bonding substrate 1 can have the same composition or different compositions, but from the point of view of manufacturing efficiency, it is preferable to have the same composition.

[0085] (2) Manufacturing method of copper-ceramic bonding substrate

[0086] Next, the manufacturing method of the bonding substrate 1 described above will be explained.

[0087] (Preparation process)

[0088] First, prepare the ceramic substrate 10, raw copper plate and brazing filler metal.

[0089] For example, oxygen-free copper plates can be used as raw material copper plates, and copper plates with P, S, As, Sb, and Zn contents within the aforementioned ranges can be appropriately selected. It should be noted that the dislocation density of the raw material copper plate is not particularly limited; for example, a density of 5.0 × 10⁻⁶ is preferred. 15 m -2 Within the following range, it can also be set to 1.0 × 10. 14 m -2 ~2.5×1015 m -2 The range.

[0090] Examples of solders containing active metals include pastes and foils. Paste-like solders can be produced by a known method of mixing metal powder composed of metallic components with an excipient containing a binder and a solvent. As mentioned above, solders may contain, for example, silver and copper as metallic components, preferably at least one active metal selected from titanium or zirconium, and may also contain at least one metallic component selected from tin or indium.

[0091] (Solder filler layer formation process)

[0092] Next, a solder paste, for example, is applied to both sides of the ceramic substrate 10. The applied solder is then dried in air or an inactive atmosphere to form a solder layer. The solder application can be performed using conventional methods such as screen printing, spraying, or roller coating. If the solder is a foil, the solder layer is formed by arranging the foil in contact with the surface of the ceramic substrate.

[0093] (Copper plate bonding process)

[0094] Next, a raw copper plate is placed in contact with the solder layer. To suppress positional displacement of the raw copper plate, temporary pressure is applied, and the laminate is heated in a vacuum or a non-oxidizing atmosphere. This melts the solder layer and bonds the raw copper plate to the ceramic substrate 10, forming a solder bonding layer 11. The raw copper plate is then bonded to the ceramic substrate 10 with the solder bonding layer 11 sandwiched between them. Furthermore, during bonding, the raw copper plate is annealed by heating, and Cu is recrystallized to reduce residual dislocations, thereby forming a copper plate 12 with a specified dislocation density. In this embodiment, by ensuring the impurity elements contained in the copper plate 12 are at the specified content described above, a dislocation density calculated by the mWH / WA method of 1.5 × 10⁻⁶ can be achieved. 13 m -2 the following.

[0095] It should be noted that "arranging the raw copper plate in contact with the solder layer" means that the ceramic substrate 10 and the raw copper plate are laminated with the solder layer sandwiched between them. Furthermore, "temporarily pressurizing the raw copper plate" means, in order to suppress positional displacement of the raw copper plate, placing a weight on the raw copper plate in the laminate, for example, through a spacer such as the ceramic substrate, or applying pressure using a jig that holds the laminate. Temporary pressurization refers to a low pressure load that can suppress positional displacement of the raw copper plate and does not cause an excessive increase in the dislocation density of the copper plate 12 obtained by bonding. If the pressure load during bonding is too high, the copper plate 12 will deform due to the bonding load during the cooling process after bonding, sometimes leading to an increase in dislocation density. Therefore, from the viewpoint of setting the dislocation density of the bonded copper plate 12 within the aforementioned range, it is acceptable to set it as a temporary pressurization based on a low pressure load. Specifically, the pressure load is preferably set to 0.5 kPa to 5 kPa.

[0096] The heating conditions during bonding can be determined by using the dislocation density in the bonded copper plate 12, calculated using the mWH / WA method, to be 1.5 × 10⁻⁶. 13 m -2 The temperature profile is adjusted appropriately as follows: Specifically, the time maintained above the softening start temperature (approximately 200°C) of Cu is adjusted so that the dislocation density falls within a specified range. From the viewpoint of shortening heating time and improving manufacturing efficiency, it is preferable to heat in a temperature range of 500°C or higher (more than twice the softening start temperature of Cu) for at least 6 hours, or more preferably, to heat in a temperature range of 700°C or higher for at least 2 hours. In the brazing method, the bonding temperature at which the raw copper plate and the ceramic substrate 10 are joined by melting the brazing filler metal is typically 750°C or higher, preferably 770°C or higher, but it is preferable to manage the temperature distribution while satisfying the aforementioned temperature range and holding time.

[0097] Thus, a bonding substrate 1 is obtained in which a copper plate 12 is bonded to a solder bonding layer 11 sandwiched on the surface of a ceramic substrate 10.

[0098] (3) Copper-ceramic circuit boards and their manufacturing methods

[0099] Next, the method for fabricating a circuit board from the aforementioned bonding substrate 1 will be described.

[0100] First, an etching resist film having a predetermined circuit pattern is formed on the surface of the copper plate 12a of the bonding substrate 1. Additionally, an etching resist film having a predetermined heat sink pattern is formed on the surface of the copper plate 12b. These resist films can be formed on the surfaces of the copper plates 12a and 12b by forming the resist using known methods such as screen printing, lamination, or photomask methods and then curing it.

[0101] Next, using known etching solutions, such as copper chloride, ferric chloride, hydrofluoric acid, chelating agents, etc., the areas of the copper plate 12 and the solder bonding layer 11 (a layer formed by the reaction of solder with the copper plate and ceramic substrate in the copper plate bonding process) that are not covered by the resist film are removed, thereby forming the prescribed circuit pattern and heat sink pattern.

[0102] Next, plating can be applied to the circuit pattern and heat sink pattern. For example, electroless Ni-P plating or electroplating Ni can be used.

[0103] Thus, the circuit board is obtained.

[0104] (4) Effects of this implementation method

[0105] According to this embodiment, one or more of the following effects are achieved.

[0106] The bonding substrate 1 in this embodiment includes a copper plate 12. The contents of S, P, As, Sb, and Zn, which are impurity elements, in the copper plate 12 are within a specified range, and the dislocation density calculated by the mWH / WA method is 1.5 × 10⁻⁶. 13 m -2 The copper plate 12 has fewer dislocations, making it easier for the Cu crystals to slide when heated, thus suppressing work hardening caused by thermal deformation. Therefore, when fabricating a power module by mounting a semiconductor chip on a circuit board obtained from the bonding substrate 1, for example, work hardening of the circuit pattern caused by heat loads such as furnace run-through during the fabrication process can be suppressed. Consequently, the increase in thermal stress applied to the ceramic substrate 10 can be suppressed, damage accumulated on the ceramic substrate 10 during fabrication can be reduced, and microcracks generated in the ceramic substrate 10 can be suppressed. Furthermore, although the power module is subjected to thermal cycling during use by generating heat when the semiconductor chip is switched on and off and cooling when its operation stops, damage to the ceramic substrate 10 can also be reduced during this thermal cycling. Thus, the bonding substrate 1 according to this embodiment can reduce damage caused by repeated thermal loads and achieve high thermal cycling performance.

[0107] Furthermore, according to the bonding substrate 1 of this embodiment, due to its high thermal cycling performance, the step shape or recess shape provided in the metal portion to alleviate the thermal stress applied to the ceramic substrate of the circuit board can be omitted. Therefore, the mounting area for mounting semiconductor chips on the surface of the circuit board can be ensured, and the overall size of the bonding substrate 1 can be avoided. Furthermore, the manufacturing process of providing the step shape or recess shape can also be omitted, thereby reducing manufacturing costs.

[0108] The average grain diameter of copper in the copper plate 12 of the bonding substrate 1 is preferably 0.05 mm to 0.5 mm. By making the average grain diameter relatively large, work hardening caused by thermal cycling can be reduced more reliably, and thermal cycling performance can be further improved.

[0109] Furthermore, in the fabrication of the bonding substrate 1 in this embodiment, a raw copper plate with S, P, As, Sb, and Zn contents within a specified range is used. Based on this raw copper plate, by setting the contents of S, P, As, Sb, and Zn, which raise the recrystallization temperature of copper, within a specified range, the rise in the recrystallization temperature of copper is suppressed. Therefore, through heating during bonding, copper can be efficiently recrystallized in the copper plate 12, dislocations in the copper plate 12 can be reduced, and its dislocation density can be set to 1.5 × 10⁻⁶. 13 m -2 the following.

[0110] Furthermore, in this embodiment, the ceramic substrate 10 and the raw copper plate are bonded (brazed) with the brazing bonding layer 11 sandwiched between them. By brazing, compared to directly bonding the ceramic substrate 10 and the raw copper plate, the heating temperature during bonding can be reduced. Therefore, the stress caused by the difference in the coefficients of thermal expansion between the ceramic substrate 10 and the raw copper plate can be reduced, and the bonding reliability between the copper plate 12 and the ceramic substrate 10 can be maintained more effectively. In addition, in the case of direct bonding, the heating temperature during bonding is higher, and there is a tendency for dislocation density to be reduced more easily through recrystallization. However, in this embodiment, since the impurity content in the raw copper plate is low, recrystallization is easier even with brazing at a lower heating temperature, thus reducing the dislocation density. In other words, in the bonding substrate 1 of this embodiment, the bonding reliability of the copper plate 12 can be improved, and the dislocation density of the copper plate 12 can be reduced.

[0111] Furthermore, in this embodiment, bonding is performed either with the ceramic substrate 10 and the raw copper plate already in place, or after placement under temporary pressure. By bonding in this manner, the bonding load applied to the copper plate 12 can be reduced. Consequently, deformation caused by the bonding load in the copper plate 12 can be suppressed, as well as the increase in dislocation density accompanying the deformation.

[0112] Other embodiments of the present invention

[0113] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the above embodiments, and various modifications can be made without departing from its spirit.

[0114] For example, in the above embodiment, the case in which the copper plate 12 is bonded to both sides (upper surface and lower surface) of the ceramic substrate 10 has been described, but in the copper-ceramic bonding substrate 1, the copper plate 12 can be bonded to at least one side of the ceramic substrate 10.

[0115] Alternatively, for example, although the mounting area is reduced, in order to further alleviate the thermal stress on the ceramic substrate 10 caused by the heat load, a stepped shape may be provided in the cross-sectional shape of the copper plate of the circuit board or a recessed shape may be provided on the outer periphery of the metal part.

[0116] Furthermore, while the above embodiments described the case of bonding the ceramic substrate 10 and the copper plate 12 with solder sandwiched between them, the present invention is not limited to this. For example, the ceramic substrate 10 and the copper plate 12 can also be directly bonded. In this case, for example, the ceramic substrate 10 and the copper plate 12 can be brought into contact and arranged without solder sandwiched between them, and then bonded by heating in an inert gas atmosphere. The heating temperature can be set to, for example, 1065°C or higher and 1083°C or lower. Furthermore, the heating time is not particularly limited as long as it ensures the reliability of the bonding between the ceramic substrate 10 and the copper plate 12.

[0117] Example

[0118] Next, the present invention will be described in more detail based on the embodiments, but the present invention is not limited to these embodiments.

[0119] <Samples 1-6>

[0120] In this embodiment, a bonding substrate is fabricated and its thermal cycling performance is evaluated.

[0121] First, in order to make the bonding substrate, prepare a ceramic substrate, raw copper plate and solder.

[0122] An AlN ceramic substrate is prepared as the ceramic substrate. The AlN substrate has dimensions of 68mm in length × 68mm in width × 0.64mm in thickness, and is divided by dividing lines so that it can be divided into four individual pieces with dimensions of 34mm in length × 34mm in width × 0.64mm in thickness.

[0123] As raw material copper plates, oxygen-free copper plates (68mm × 68mm × 0.25mm in size) with a copper purity of 99.96% by mass or higher and an alloy number / quality category of C1020-1 / 2H are prepared. In this embodiment, as shown in Table 1, six types of oxygen-free copper plates, namely copper plate A to copper plate F, are prepared.

[0124] [Table 1]

[0125]

[0126] In Table 1, the content of impurity elements in copper plates A through F was determined by glow discharge mass spectrometry (GDMS). Specifically, firstly, sample pieces approximately 25 mm square were cut from each raw copper plate. Next, the surface of the sample pieces was cleaned with nitric acid to remove contamination. The content of impurity elements was then determined using a GDMS apparatus (VG Elemental, "VG9000"). In Table 1, "Total amount of other impurity elements" indicates the total amount of elements not listed in the table. It should be noted that the values ​​in Table 1 are based on GDMS measurements; therefore, "other impurity elements" does not include H, C, N, O, Group 18 elements, or Ta (used as the sample holder in the GDMS apparatus), which cannot be quantitatively evaluated using GDMS.

[0127] The determination conditions for GDMS are set as follows: A flat cell (for flat samples) is used as the discharge unit (ion source), and liquid nitrogen is used to cool the discharge unit during analysis. High-purity Ar gas of grade 6N is used as the discharge gas. The glow discharge is set to a constant current control mode of 3mA, and the discharge voltage is controlled to 1kV by the amount of discharge gas introduced. For the detection and measurement of ion current, a Faraday detector is used for Cu as the matrix element, and a Daly detector is used for other impurity elements. The integration time of the detector is 160ms × 1 acquisition time for the Faraday detector, and 200ms × 3–5 acquisition times for the Daly detector. The mass resolution (m / Δm: 5% peak height) is adjusted to approximately 4000 or higher. The relative sensitivity factor (RSF) used to convert the ion current intensity ratio to concentration is the value built into the device. It should be noted that the determination of ion current values ​​used in quantitative analysis is performed after surface contamination has disappeared due to pre-discharge (approximately 20 minutes) and the ion intensity ratios of each element have stabilized.

[0128] The solder is prepared as follows. 100 parts by weight of a powder consisting of 10% copper powder, 1.7% titanium powder, 0.5% titanium oxide powder (titanium oxide (IV) rutile type), and the remainder being silver powder are weighed out. 13.8 parts by weight of an excipient consisting of an acrylic binder and solvent are added relative to these 100 parts by weight of the powder. The mixture is then kneaded using a mortar and three-roll mill to prepare a paste-like solder.

[0129] Next, a copper-ceramic bonding substrate is fabricated using the prepared materials.

[0130] Specifically, firstly, a paste-like solder is applied to both sides of an AlN ceramic substrate. Then, the paste-like solder is screen-printed onto approximately the entire surface of each of the four partitions defined by dividing lines within the AlN ceramic substrate, resulting in a thickness of approximately 20 μm. The solder-coated AlN ceramic substrate is then dried in atmospheric air to form a solder coating layer.

[0131] Next, copper plates A to F were respectively placed in contact with both sides of an AlN ceramic substrate through a solder coating layer to form a laminate. The laminate was then introduced into a vacuum furnace under a pressure of 1 kPa, with a weight placed between the ceramic substrate (alumina substrate) and a spacer. In the vacuum furnace, it was heated to a bonding temperature (maximum temperature) of 835°C for 40 minutes and then cooled. It should be noted that the temperature range above 500°C was maintained for 7.5 hours during the series of heating, holding, and cooling processes. Similarly, the temperature range above 700°C was maintained for 2.5 hours during the same process. Thus, copper plates A to F were bonded to an AlN ceramic substrate to create copper-ceramic bonded substrates, which were then used as samples 1 to 6.

[0132] (Fabrication of circuit boards)

[0133] Next, circuit patterns and heat sink patterns are formed on the copper-ceramic bonding substrate.

[0134] Specifically, an etching mask with a circuit pattern shape was applied to the surface of the copper plate on one side of the bonding substrates of samples 1-6, and an etching mask with a heat sink pattern shape was applied to the surface of the copper plate on the other side. This was achieved by applying a UV-curable alkaline stripping resist ink using screen printing and then UV curing. Afterwards, unwanted portions of the copper plate and the solder bonding layer (areas not covered by the etching mask) were removed using a chemical solution, and then the etching mask was removed using an alkaline solution. The laminate containing the circuit pattern and heat sink pattern was then divided into four sections along a dividing line on the AlN ceramic substrate. A 4μm thick Ni-P coating was then formed on each of the divided laminates using a chemical Ni-P plating method to create a copper-ceramic bonding substrate (34mm × 34mm). The circuit pattern shape and heat sink pattern shape of this circuit substrate (metal-ceramic bonding substrate) are as follows: Figure 2 and Figure 3 As shown. Figure 2 This is a schematic diagram illustrating the shape of a circuit pattern formed on one side of the bonding substrate in an embodiment. Figure 3 This is a schematic diagram illustrating the shape of the heat sink pattern formed on the other side of the bonding substrate in the embodiment.

[0135] (Evaluation Method)

[0136] For circuit boards obtained from the bonding substrates of samples 1 to 6, the average grain diameter and dislocation density in the copper plate, the peel (bonding) strength between the copper plate and the ceramic substrate, the bending strength of the circuit board, and the furnace pass resistance were measured and evaluated. Peel strength and bending strength are indicators related to the damage accumulated in the ceramic substrate during the bonding substrate manufacturing process (the proportion of microcracks in the ceramic). Higher strengths indicate less damage accumulated in the ceramic substrate in the final bonding substrate, resulting in higher thermal cycling performance. On the other hand, furnace pass resistance is a value evaluating the effect of heating during the assembly of power modules using the circuit board; it is an accelerated test simulating the heat treatment (thermal cycling) of the circuit board during assembly. The measurement methods are explained below.

[0137] (Average grain diameter in copper plate)

[0138] The grain diameter of the copper plate was evaluated using the cutting method described in JIS H 0501. Specifically, it is as follows: First, the surface of the copper plate of the bonding substrate was etched using an etching solution for observing copper microstructure to make the grains easily identifiable, and then an optical microscope image was taken (100x magnification, field of view size 3.5mm × 2.6mm). An evaluation line segment (3.5mm in length) for the cutting method was drawn in the center of the obtained image, and the number of crystals cut by the line segment was counted. The number of crystals was divided by the cutting length of 3.5mm to calculate the grain size in that field of view. This operation was performed on any 5 fields of view, and the average value was taken as the average grain diameter of the bonding substrate.

[0139] (Dislocation density of a copper plate)

[0140] The dislocation density of the copper plate was measured using X-ray diffraction profilometry (mWH / WA method) on the circuit board (laminar) obtained before electroless Ni-P plating. Specifically, firstly, the laminate was chemically polished for 5 minutes in a chemical polishing slurry (45°C) consisting of 14% sulfuric acid, 3.2% hydrogen peroxide, and the balance water to remove surface defect layers that might have been generated during processing. This removed the surface defect layer formed on the copper plate surface. Then, for the chemically polished laminate, the dislocation density of the copper plate was measured using X-ray diffraction profilometry (mWH / WA method) at the central part of the copper plate surface with the heat sink pattern.

[0141] Dislocation density was measured using an X-ray diffraction apparatus (Rigaku Corporation's "SmartLab"). The X-ray source was a Cu tube sphere (tube voltage 45 kV, tube current 200 mA), which monochromated into CuKα rays by a multilayer reflector on the incident side. Furthermore, the optical system (configuration of the X-ray source and detector) was set to a symmetrical reflection method (focusing method).

[0142] In the analysis of the X-ray line profile obtained by measurement, the four peaks (220), (311), (331), and (420) of the Cu diffraction plane were used to remove Kα2 composition and background using the Ladell method. Furthermore, the line profile variation originating from the measurement system was determined by measuring a standard sample (a sample obtained by heating a 99.96% pure copper plate (manufactured by Nilaco Corporation) in a vacuum furnace at 750°C for 6 hours), and this variation was used to correct the apparatus constant using the Stokes method, thereby eliminating the influence of line profile expansion caused by measurement system factors (apparatus factors). Additionally, the value of the constant term Ch00 used in the mWH / WA method was 0.304, as reported for pure copper.

[0143] (Peel strength)

[0144] For circuit boards, use a portion of the circuit pattern with a pattern width of 3mm. Figure 2 The topmost pattern was used to determine the peel strength using a 90° peel method (according to JIS C 5016, crosshead speed 50 mm / min). In this embodiment, five circuit boards were evaluated, and the average of the measurements at five locations was taken as the peel strength.

[0145] (Flexural strength)

[0146] Bending strength was measured by performing a three-point bending strength test (according to JIS C2141, with a distance of 30 mm between the lower support points, the circuit pattern surface positioned below, and the load applied from above). In this embodiment, five circuit boards were evaluated, and their average value was taken as the bending strength.

[0147] (Furnace tolerance)

[0148] The furnace endurance was evaluated using a batch furnace with internal carbon hot plates and a water-cooled cooling plate on the lower surface opposite the hot plates that could be switched between contact and non-contact by lifting and lowering.

[0149] Specifically, the circuit board is placed on the upper surface of the hot plate of the batch furnace, and repeated furnace-passing heat loads are applied. The temperature distribution of one furnace-passing heat load is as follows: the hot plate is heated to a maximum temperature of 380°C at an average heating rate of approximately 1.0°C / s without the cooling plate in contact with the hot plate. This maximum temperature of 380°C is then maintained for 10 minutes, allowing the cooling plate to come into contact with the hot plate, followed by rapid cooling to room temperature (average cooling rate of approximately 2.5°C / s from 380°C to 100°C, and average cooling rate of approximately 0.5°C / s from 100°C to 40°C). This process is considered one furnace-passing heat load. The atmosphere inside the batch furnace during the furnace-passing process is a reducing atmosphere with a hydrogen / nitrogen ratio of 20 / 80 (capacity%).

[0150] Then, the circuit board was repeatedly subjected to furnace heat load. Every three furnace heat loads, the ceramic substrate of the circuit board was examined under a microscope. The number of times a crack was first found on the ceramic substrate was recorded as the furnace heat load value for that single piece. This furnace heat load value was applied to 10 circuit boards, and Weibull plot analysis was performed on the results to estimate the Weibull distribution of the furnace heat load. The expected value of the Weibull distribution was calculated from the estimated Weibull distribution, and the result was used as the expected value of the furnace heat load.

[0151] It should be noted that, since the circuit board has a chemically plated Ni-P coating, it is more prone to cracking of the ceramic substrate due to heat load compared to the unplated state. Compared to the unplated state, the evaluation can be completed with fewer furnace heat load cycles.

[0152] (Evaluation Results)

[0153] The evaluation results are summarized in Table 2.

[0154] [Table 2]

[0155]

[0156] In samples 1-5, it was confirmed that, due to the use of copper plates A-E with P, S, As, Sb, and Zn contents within the specified range, the dislocation density in the copper plate could be adjusted to 1.5 × 10⁻⁶ when fabricating a bonding substrate by bonding it with a ceramic substrate. 13 m -2 Furthermore, in the circuit boards made from the bonding substrates of samples 1 to 5, the peel strength was 300 N / cm or more, and the flexural strength was 400 MPa or more. This confirms that damage to the ceramic substrate (the generation of microcracks) caused by heat load during the circuit board manufacturing process can be suppressed. Additionally, since the furnace pass tolerance was 8 times or more, it was confirmed that damage to the ceramic substrate could be suppressed even under repeated heat loads on the circuit board. It should be noted that samples 1 to 3, in particular, with 15 or more furnace pass tolerances, are excellent in this invention.

[0157] In contrast, in sample 6, it was confirmed that due to the use of copper plates F containing more S, As, Sb, and Zn than specified, the dislocation density in the copper plates of the bonding substrate was as high as 2.2 × 10⁻⁶. 13 m -2This is presumably because there is an abundance of S, As, Sb, and Zn, which raise the recrystallization temperature, while there is a deficiency of P, which inhibits the rise in recrystallization temperature caused by S. Consequently, Cu cannot recrystallize efficiently during bonding, and dislocations cannot be reduced. Furthermore, in sample 6, compared to samples 1-5, lower peel strength and flexural strength were observed. This suggests that work hardening of the copper plate during circuit board fabrication increases the thermal stress applied to the ceramic substrate, leading to damage. Additionally, a low furnace withstand capacity was confirmed, resulting in repeated application of thermal loads to the circuit board, which easily damages the ceramic substrate.

[0158] As described above, by using a copper plate with P, S, As, Sb and Zn contents within a specified range in the bonding substrate, the dislocation density in the copper plate can be reduced by heating during bonding with the ceramic substrate, thereby achieving high thermal cycling performance.

[0159] Explanation of reference numerals in the attached figures

[0160] 1 Copper-Ceramic Bonded Substrate

[0161] 10 Ceramic Substrates

[0162] 11 Brazing filler layer

[0163] 12 copper coins

Claims

1. A copper-ceramic bonding substrate, comprising: Ceramic substrates; and A copper plate already bonded to at least one side of the ceramic substrate. The dislocation density on the surface of the copper plate, measured by the modified Williamson-Hall / Warren-Averbach method, is 1.5 × 10⁻⁶. 13 m -2 the following, The copper plate contains 0.05 ppm to 0.5 ppm of arsenic and 0.02 ppm to 0.2 ppm of antimony. The copper plate contains 0.1 ppm to 7 ppm of sulfur and 0.05 ppm to 2 ppm of phosphorus. The zinc content in the copper plate is 0.005ppm to 0.08ppm. The silver content in the copper plate is 0.1 ppm to 20 ppm. The total amount of impurity elements in the copper plate, excluding sulfur, phosphorus, arsenic, antimony, zinc and silver, is 0.01 ppm to 15 ppm.

2. The copper-ceramic bonding substrate according to claim 1, wherein, The copper plate is made of oxygen-free copper or tough copper.

3. The copper-ceramic bonding substrate according to claim 1 or 2, wherein a solder bonding layer is provided between the ceramic substrate and the copper plate. The copper plate sandwiches the brazing solder layer and is bonded to the ceramic substrate.

4. A method for manufacturing a copper-ceramic bonding substrate, comprising the following bonding step: depositing a copper plate with an arsenic content of 0.05ppm to 0.5ppm and an antimony content of 0.02ppm to 0.2ppm on at least one side of a ceramic substrate and bonding them by heating. The copper plate contains 0.1 ppm to 7 ppm of sulfur and 0.05 ppm to 2 ppm of phosphorus. The zinc content in the copper plate is 0.005ppm to 0.08ppm. The silver content in the copper plate is 0.1 ppm to 20 ppm. The total amount of impurity elements in the copper plate, excluding sulfur, phosphorus, arsenic, antimony, zinc, and silver, is 0.01 ppm to 15 ppm. The dislocation density on the surface of the joined copper plate, measured by the modified Williamson-Hall / Warren-Averbach method, was 1.5 × 10⁻⁶. 13 m -2 the following.

5. The method for manufacturing a copper-ceramic bonding substrate according to claim 4, wherein, In the bonding process, the copper plate is placed on the ceramic substrate, and the ceramic substrate and the copper plate are heated under temporary pressure.

6. The method for manufacturing a copper-ceramic bonding substrate according to claim 4 or 5, wherein, The copper plate is made of oxygen-free copper or tough copper.

7. The method for manufacturing a copper-ceramic bonding substrate according to claim 4 or 5, wherein, After the copper plate is sandwiched with the brazing filler metal and placed on the ceramic substrate, it is heated to join them.

8. The method for manufacturing a copper-ceramic bonding substrate according to claim 4 or 5, wherein, In the joining process, heating is performed at a temperature of 500°C or higher for more than 6 hours.

9. The method for manufacturing a copper-ceramic bonding substrate according to claim 4 or 5, wherein, In the joining process, heating is performed at a temperature of 700°C or higher for more than 2 hours.

10. The method for manufacturing a copper-ceramic bonding substrate according to claim 4 or 5, wherein, The temporary pressurization load pressure in the joining process is 0.5 kPa to 5 kPa.

Citation Information

Patent Citations

  • Manufacture of ceramic wiring board

    JP1996097554A

  • High-reliability substrate for semiconductors

    JP1998125821A

  • Insulation substrate, manufacturing method thereof, and power semiconductor device

    JP2012114203A

  • Pure copper plate

    WO2021177469A1